Retrenchment: the law and practice in Malaysia - Ali Mohamed, Ashgar Ali; Sardar Baig, Farheen Baig (Thomson Reuters Asia Sdn Bhd, 2020)
This book, Retrenchment: the law and practice in Malaysia (2nd Edition), which consists of 18 chapters, provides an extensive coverage on the retrenchment law and practices in Malaysia with a detailed guide to most of the salient aspects of this subject.